THE EFFECT OF E-ADMINISTRATION PROFICIENCY ON ORGANIZATIONAL COMPETITIVENESS AND PERFORMANCE AMONG CORPORATE EMPLOYEES - Abdulraheem Y. O. AL Abdiy (Scholars Digest Publishing, 2025)
The possibility of electronic driving has become a necessity today. This article provides a basic overview of commendable and contemporary energy methods for managing the impact of electronic leadership capabilities on the work approach of delegates working in associations, and identifies the essential and essential capabilities of effective experts in the electronic age. Electronic changes have brought about tremendous changes in the business environment. The pioneers must change according to another plan for the problems and expected results. This has led to increased interest in building electronic organizational boundaries and capabilities. While messaging, vision and progress have been highlighted as compelling gifts in the cyber domain, clearer statements about critical exceptional capabilities are needed. Progress in the information age. E-aggregation, e-development, e-change, and e-community significantly influence agent performance, motivation, satisfaction, and commitment. As this research has shown, cyber power leads to improved employee performance, improved cyber capabilities, and achieving company goals in an ever-changing cyber world. E-Leadership is a pioneering initiative to which everyone is committed.
Keywords: Company Business Success, Cyber Power, Digital Skills, Digital transformation, E-Leadership, Employee behavior, Job Performance